Can a short neuromuscular warmup before tackling improve shoulder joint position sense in rugby players? - Baker, S. P.; Fulcher, M. L.; Exeter, D. J.; McMorland, A. J.; Sahni, M. (The Journal of Sports Medicine and Physical Fitness, 2020)
BACKGROUND: In rugby the tackle is a complex task requiring joint position sense (JPS). Injuries commonly occur during the tackle and these account for significant time lost from training and play. Simulated tackling tasks have previously shown a reduction in shoulder joint position sense and it is possible that this may contribute to injury. There is growing evidence in support of injury prevention programs, but none so far are dedicated specifically to tackling. We postulate that a brief neuromuscular warmup could alter the negative effects of fatigue on shoulder JPS. METHODS: In this field based, repeated measures design study, 25 semi-professional Rugby players participated. JPS was measured at criterion angles of 45° and 80° of right arm shoulder external rotation. Reproduction accuracy prior to and following a neuromuscular warmup and simulated tackling task was then assessed. RESULTS: In pre-warmup JPS measures, the spread of angle errors were larger at the 80° positions. Adding the warmup, the spread of the angle errors at the 80° positions decreased compared to pre-intervention measures. Two one-sided tests (TOST) analysis comparing pre- and post-testing angle errors, with the addition of the warmup, indicated no difference in JPS. CONCLUSIONS: The neuromuscular warmup resulted in a decrease in JPS error variance meaning fewer individuals made extreme errors. The TOST analysis results also suggest the neuromuscular warmup used in this study could mitigate the negative effects of tackling on JPS that has been seen in prior research. This neuromuscular warmup could play a role in preventing shoulder injuries. It can easily be added to existing successful injury prevention programs.